Tramadol and Propentofylline Coadministration Exerted Synergistic Effects on Rat Spinal Nerve Ligation-Induced Neuropathic Pain - Zhang, Jin; Wu, Dan; Xie, Cheng; Wang, Huan; Wang, Wei; Zhang, Hui; Liu, Rui; Xu, Li-Xian; Mei, Xiao-Peng (PLOS ONE, 2013)
Neuropathic pain is an intractable clinical problem. Drug treatments such as tramadol have been reported to effectively decrease neuropathic pain by inhibiting the activity of nociceptive neurons. It has also been reported that modulating glial activation could also prevent or reverse neuropathic pain via the administration of a glial modulator or inhibitor, such as propentofylline. Thus far, there has been no clinical strategy incorporating both neuronal and glial participation for treating neuropathic pain. Therefore, the present research study was designed to assess whether coadministration of tramadol and propentofylline, as neuronal and glial activation inhibitors, respectively, would exert a synergistic effect on the reduction of rat spinal nerve ligation (SNL)-induced neuropathic pain. Rats underwent SNL surgery to induce neuropathic pain. Pain behavioral tests were conducted to ascertain the effect of drugs on SNL-induced mechanical allodynia with von-Frey hairs. Proinflammatory factor interleukin-1β (IL-1β) expression was also detected by Real-time RT-PCR. Intrathecal tramadol and propentofylline administered alone relieved SNL-induced mechanical allodynia in a dose-dependent manner. Tramadol and propentofylline coadministration exerted a more potent effect in a synergistic and dose dependent manner than the intrathecal administration of either drug alone. Real-time RT-PCR demonstrated IL-1β up-expression in the ipsilateral spinal dorsal horn after the lesion, which was significantly decreased by tramadol and propentofylline coadministration. Inhibiting proinflammatory factor IL-1β contributed to the synergistic effects of tramadol and propentofylline coadministration on rat peripheral nerve injury-induced neuropathic pain. Thus, our study provided a rationale for utilizing a novel strategy for treating neuropathic pain by blocking the proinflammatory factor related pathways in the central nervous system.